Isolation and characterization of a N,N'-dicyclohexylcarbodiimide-resistant mutant of Methanothermobacter thermautotrophicus with alterations to the ATP synthesis machinery - Nováková, Zuzana; Majerník, Alan; Bobáľová, Janette; Vidová, M; Šmigáň, Peter (Folia microbiologica, 2009)
A spontaneous mutant of Methanothermobacter thermautotrophicus resistant toward the ATP-synthase inhibitor N,N'-dicyclohexylcarbodiimide (DCCD) was isolated. DCCD normally inhibits methanogenic electron-transport-driven ATP synthesis, however, the DCCD-resistant strain exhibited methanogenesis in the presence of 300 micromol/L DCCD. Total ATP synthesis was shown to be higher in the mutant strain, both in the presence and absence of DCCD. These results suggested a modification in the ATP-synthesizing system of the mutant strain. Using Blue Native PAGE combined with MALDI TOF/TOF mass spectrometry, increased concentrations of both the A(1) and A(o) subcomplexes of the A(1)A(o)-type synthase were identified in the mutant strain. However, no alterations were found in the structural genes (atp) for the A(1)A(o) ATP synthase. The results imply that DCCD resistance is a consequence of increased A(1)A(o) ATP synthase expression, and suggest that genes involved in regulating synthase expression are responsible for DCCD resistance.
Keywords: mutace; Archaeal Proteins; financování organizované; Electrophoresis, Polyacrylamide Gel; Methanobacteriaceae; Drug Resistance; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Proton-Translocating ATPases; Up-Regulation; Dicyclohexylcarbodiimide; léková rezistence; Enzyme Inhibitors; protonové ATPasy; upregulace; Mutation; adenosintrifosfát; dicyklohexylkarbodiimid; Financing, Organized; oxidace-redukce; methan; Adenosine Triphosphate; Oxidation-Reduction; archeální proteiny; inhibitory enzymů; exprese genu; Methane; spektrometrie hmotnostní - ionizace laserem za účasti matrice; elektroforéza v polyakrylamidovém gelu; Gene Expression